Assessment of heavy metals in sediments and edible shellfish from Youtefa Bay, Papua, Indonesia - ROSYE HEFMI RECHNELTY TANJUNG; ERVINA INDRAYANI; LALU PANJI IMAM AGAMAWAN; BAIGO HAMUNA (Society for Indonesian Biodiversity, 2026)
Abstract. Tanjung RHR, Indrayani E, Agamawan LPI, Hamuna B. 2026. Assessment of heavy metals in sediments and edible shellfish from Youtefa Bay, Papua, Indonesia. Biodiversitas 27 (4): d270428. https://doi.org/10.13057/biodiv/d270428. The main gaps in the environmental quality research on Youtefa Bay are the lack of comprehensive information on heavy metal contamination in sediments and consumable biota, and the absence of a temporal evaluation linking changes in metal content to potential ecological and public health risks. This study aims to assess eight heavy metals simultaneously (Hg, Pb, As, Cr, Cd, Ni, Zn, and Cu) in sediments and edible shellfish from Youtefa Bay, Indonesia, and evaluate ecological and food safety risks through contamination factor (CF), ecological risk index (Ei, ERI), biota-sediment accumulation factor (BSAF), and multivariate analyses. Analysis of metal content in sediments and shellfish was performed using Atomic Absorption Spectrometry instruments with QA/QC procedures and reported based on dry-weight. Sediment results revealed elevated Ni content, reaching up to 401 mg/kg at St.3, exceeding threshold effect levels (TEL), while Cd showed the highest ecological risk contribution, with Ei values up to 126 at St.3, indicating moderate ecological risk. In sediments, the order of heavy metal content is Ni > Cr > Zn > Cu > Pb > Cd > As > Hg. BSAF analysis indicated species-specific accumulation patterns, with higher bioaccumulation potential for Cd and Cu in certain taxa. Principal component analysis (PCA) explained 81.3% of total variance, separating Ni-dominated sediment signals from Cd-associated ecological risk patterns. Although spatial variability was evident, overall findings indicate localized metal enrichment and potential health concerns, particularly for Cd. The accumulation of Cd, Ni, and Zn in all three shellfish species exceeded international safe consumption limits (FAO and WHO), indicating a potentially serious health risk to the surrounding community. Overall, the results of this study highlight potential ecological and food security concerns and emphasize the need for continued monitoring and improved pollution management in Youtefa Bay.